Rekayasa Waktu Dan Temperatur Penyulingan Untuk Peningkatan Rendemen Minyak Atsiri Kulit Jeruk Lemon (Citrus Limon. L) - Fadila, Abil; Nurjanah, Sarifah; Rosalinda, Rosalinda (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2026)
Lemon processing generates a substantial amount of peel waste, accounting for approximately 40-50% of the total fruit weight. The lemon peel, particularly the flavedo layer, contains essential oil compounds with the potential to be developed into value-added products through distillation. This study evaluates the influence of distillation duration and temperature parameters on the yield and physicochemical quality of essential oil derived from lemon peel waste. The experiment employed a Factorial Completely Randomized Design (CRD) with two factors: distillation time (P = 4, 5, 6, 7, and 8 hours) and distillation temperature (T = 83, 90, 100, 110, and 117°C). The observed parameters included oil yield, specific gravity, refractive index, acid value, and solubility in 70% alcohol. Data were processed using Analysis of Variance (ANOVA) followed by Duncan's Multiple Range Test (DMRT) at a 95% confidence level. The findings indicate that distillation time significantly affects the essential oil yield, whereas temperature variations within the tested range do not show a significant impact. The highest yield of 0.84% was achieved at a distillation time of 8 hours at 100°C. The resulting essential oil exhibited a specific gravity of 0.851 g/mL, a refractive index of 1.473, an acid value of 5.60 mg KOH/g, and a 1:10 solubility in 70% alcohol, all of which meet quality standards. These results demonstrate that optimizing distillation conditions can enhance yield while maintaining the quality of lemon peel essential oil.